Sinus metastasis of lung adenocarcinoma: a case report - Xu, Mingyuan; Sun, Qi; Lv, Xin; Chen, Fangjun; Su, Shu; Wang, Lifeng (Frontiers in Medicine, 2024)
Metastatic carcinoma of the paranasal sinuses in lung cancer is an extremely uncommon condition. We report here a 57-year-old female patient with epidermal growth factor receptor (EGFR)-positive stage IV non-small cell lung cancer (NSCLC) with multiple bone metastases. After resistance to second-and third-generation EGFR-tyrosine kinase inhibitors (TKIs), the patient presented with headache accompanied by progressively enlarging lesions of the nasal cavity on CT scan. Further endoscopic sinus neoplasmectomy confirmed sinus metastasis of lung adenocarcinoma.Although subsequent chemotherapy and immunotherapy were both administered, the disease continued to progress, and the patient passed away 21 months after diagnosis. Combined with real-time dynamic nextgeneration sequencing (NGS) during the different generations of EGFR-TKI treatments and dynamic tumour microenvironment analysis, we discussed the clinical manifestations of sinus metastasis and the molecular biology and tumour immune microenvironment changes after resistance to the second-and third-generation of EGFR-TKI therapy.Introduction: Lung cancer is a disease prone to multiple systemic metastases, common metastases including brain, bone, liver, lymph nodes, adrenal glands, thoracic cavity, and so on (1). Clinically, it is very rare for lung cancer to metastasize to unusual sites, such as the paranasal sinuses.Here, we report a patient with advanced lung cancer with EGFR-sensitive mutation who presented with recurring headaches during sequential second-and third-generation EGFR-TKI therapy, and it turned out to be sinus metastasis of lung adenocarcinoma by the following imaging and pathological examination. Unfortunately, the patient did not respond well to subsequent platinum-based doublet chemotherapy or immune therapy.Previous clinical data showed that EGFR-positive patients have a limited response to immunotherapy, and the underlying mechanism is uncertain(2, 3). Based on the patient's multiple prebiopsy tissue samples, dynamic NGS tests and the tumour microenvironment were further analyzed. We discuss this rare metastasis of lung cancer in terms of molecular biology, tumour immune microenvironment characteristics, and possible effects of sequential treatments on the evolution of tumour biological features.